2015
DOI: 10.3402/tellusb.v67.27721
|View full text |Cite
|
Sign up to set email alerts
|

On the complexity of the boundary layer structure and aerosol vertical distribution in the coastal Mediterranean regions: a case study

Abstract: A B S T R A C TThe planetary boundary layer structure in the coastal areas, and particularly in complex orography regions such as the Mediterranean, is extremely intricate. In this study, we show the evolution of the planetary boundary layer based on in situ airborne measurements and ground-based remote sensing observations carried out during the MORE (Marine Ozone and Radiation Experiment) campaign in June 2010. The campaign was held in a rural coastal Mediterranean region in Southern Italy. The study focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…x ARTS matches the a priori profile from 12 km of altitude upward and, below 9 km, it is consistent with the measurements of precipitable water vapor (PWV) collected by the HATPRO radiometer (Rose and Czekala, 2009;Pace et al, 2015) installed at the THAAO. This lower part of x ARTS is calculated according to x ARTS (from the ground to 9 km) = PWV Hatpro PWV Eu…”
Section: Forward Model and A Priori Profilessupporting
confidence: 55%
See 1 more Smart Citation
“…x ARTS matches the a priori profile from 12 km of altitude upward and, below 9 km, it is consistent with the measurements of precipitable water vapor (PWV) collected by the HATPRO radiometer (Rose and Czekala, 2009;Pace et al, 2015) installed at the THAAO. This lower part of x ARTS is calculated according to x ARTS (from the ground to 9 km) = PWV Hatpro PWV Eu…”
Section: Forward Model and A Priori Profilessupporting
confidence: 55%
“…The forward model is provided by the ARTS software (Eriksson et al, 2011), which is tuned to reproduce the VESPA-22 measurement technique. In order to perform a realistic simulation of the troposphere, the PWV measured by the HATPRO radiometer (Rose and Czekala, 2009;Pace et al, 2015) operating side by side with VESPA-22 is taken into account in the forward model.…”
Section: Discussionmentioning
confidence: 99%
“…Junkermann, 2001;Meloni et al, 2003;Di Iorio et al, 2003;Pace et al, 2015) and eastern (e.g. Formenti et al, 2002;Dulac and Chazette, 2003) parts of the basin thus improving the description of the atmospheric composition and structure over the whole Mediterranean area.…”
Section: Discussionmentioning
confidence: 99%
“…Aitken particle profiles are very rare over the sea surface in the Mediterranean (e.g. Junkermann et al, 2001;Pace et al, 2015) and data comparison is quite difficult. A few studies have observed NPF in the FT in continental areas Rose et al, 2015) and suggest that the export of pollution into the upper troposphere, as is common in the western basin, might promote the occurrence of these events.…”
Section: Discussionmentioning
confidence: 99%
“…The profile is the profile used in the forward model calculations to compute the apriori spectrum and the weighting functions. matches the apriori profile from 12 km of altitude upward and, below 9 km, it is consistent with the measurements of precipitable water vapor (PWV) collected by the HATPRO radiometer (Rose and Czekala, 2009;Pace et al, 2015) The pressure and temperature profiles needed to run the forward calculation are built merging NASA Goddard Space Flight Center (GSFC), AURA/MLS and climatological temperature and pressure profiles. The NASA GSFC profiles by Goddard…”
Section: Distribution 10mentioning
confidence: 59%